Vnetja v obporodnem obdobju - Assejev, Vladimira (Zdravniški vestnik, 2003)
Background. Around 6% of preterm newborns contribute to the 75% perinatal mortality rate. Besides, these newborns are more prone to morbidity. Despite numerous studies and measures the overall preterm delivery rate over the last decade has not decreased. Namely, spontaneous preterm delivery rate has been decreasing, yet the indicated preterm delivery rate has been increasing. Thereare numerous factors triggering a preterm delivery, one of them being infections. This study is the second in our series of papers dealing with preterm delivery. The aim of this study was to find whether there exists, together with other risk factors, a relationship between gynecological and obstetrical anamnestic data and preterm delivery. Methods. For 133 mothers andtheir preterm babies (study group) and 127 mothers and their term babies (control group), a questionnaire was filled-in after delivery. Results. Significant differences regarding infections between the study and control group were found in anamnestic data regarding the use of antibiotics in current pregnancy (except for urinary tract infection) and use of antibiotics during current delivery. Besides these, significant differences were observed also in connection with a previous preterm delivery, the interval between a previous and current delivery of less than two years, conization, use of tocolytics in current pregnancy, sick leave in current pregnancy, diseases in current pregnancy which actually led to indicated preterm delivery in favour of mother condition. Conclusions. Pregnant women who delivered preterm, were significantly more often treated with antibiotics in current pregnancy. These pregnant women should be regarded as more prone to preterm delivery. There were no such differences regarding colpitis and cervicitis treatment in current pregnancy or gynecological infections treatment before pregnancy. (Abstract truncated at 2000 characters).
Keywords: antibiotic; Antibiotics; Antibiotiki; Dejavniki tveganja; Etiology; human pregnancy; Labor, Premature; Nosečnost; novorojenčki; Porod prezgodnji; porodnice; Pregnancy; prezgodnji porod; Risk Factors; Therapeutic Use; vnetja